All that is mine I carry with me : a novel - Landay, William (New York : Bantam, 2023)
Jane Larkin disappeared without a trace in November 1976. Ten-year-old Miranda arrives home from school, finds her mother's pocketbook in its usual spot, and assumes her mother will be back any minute. As the hours tick by, Miranda becomes filled with certainty that her mother will never come home again. In the absence of other leads, detectives turn their suspicions toward Jane's husband, Daniel. No evidence is ever found, nor is any real motive. Miranda and her brothers, are left in limbo.
Keywords: Missing persons -- Fiction; Family secrets -- Fiction; Revenge -- Fiction; Siblings -- Fiction; Cold cases (Criminal investigation) -- Fiction; Loyalty -- Fiction; Thrillers (Fiction); Detective and mystery fiction